Developing a sensor based alerting system for stroke patients‟ safety - Ramalingam, Mritha; Puviarasi, R.; Chinnavan, Elanchezhian; Nur Sofea Iznie, Johan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
With the expanding number in the elderly populace, as well as the changes in lifestyle emergence that causes several chronic diseases. Stroke is one of the main chronic disease that leads to disability and death. So, it is necessary to monitor the health status of the patients to prevent from fatal disorders. If affected by stroke, in order to improve the function and gain as much independent as possible, the stroke patients have to do some rehabilitation. The selection of medicinal services innovation is promising to improve the personal satisfaction for endless illness patients and the elderly and an individual. This paper proposes a promising innovation by discussing some of the existing, related works. This paper is aimed to develop a system that can measure stroke patients’ vital sign during their rehabilitation using microcontroller and sensor technology. As a result, the system will prevent the patients to suffer from further stroke or fatal. Also, the system will produce alarm as an alert to the assisting person of the patient.